PENERAPAN METODE KOOPERATIF TIPE TALKING STICK TERHADAP HASIL BELAJAR PAI - Haerudin . (LPPM Universitas Buana Perjungan Karawang, 2018)
Abstract: This study aims to examine how much the effectiveness of the application of cooperative learning method of Talking Stick Type to the learning outcomes of Religious Education in SD Negeri I Plawad, in order to improve the learning outcomes in the elementary school, and to know how much student response to the application of cooperative learning model with Talking Stick model. This research was conducted with research subjects of V student of SD Negeri I Plawad karawang academic year 20017/2018. The research method used is class action method (PTK) consisting of 2 cycles, each cycle consists of 2 meetings. Data collection through pretest, posttes, observation, questionnaires, field notes, and interviews. From the results of this study, the researcher hopes to give contribution and benefit for all related parties, especially the school in order to improve the learning result especially in the field of PAI lesson generally for other lessons, so it can be useful also for other schools in general. Keywords: Learning Talking Stick, Learning Outcomes. Abstrak: Penelitian ini bertujuan untuk menelaah seberapa besar efektifitas penerapan pembelajaran metode cooperative learning Tipe Talking Stick terhadap hasil belajar Pendidikan Agama di SD Negeri I Plawad, guna meningkatkan hasil belajar di SD tersebut, dan mengetahui seberapa besar respon siswa terhadap penerapan model pembelajaran kooperatif dengan model Talking Stick. Penelitian ini dilakukan dengan subjek penelitian siswa kelas V SD Negeri I Plawad karawang tahun ajaran 20017/2018. Metode penelitian yang di gunakan adalah metode tindakan kelas (PTK) yang terdiri dari 2 siklus, setiap siklus terdiri dari 2 pertemuan. Pengumpulan data melalui pretest, posttes, observasi, angket, catatan lapangan, dan wawancara. Dari hasil penelitian ini peneliti berharap agar dapat memberikan kontribusi dan manfaat bagi semua pihak-pihak yang terkait, terutama pihak sekolah dalam rangka peningkatan hasil belajar khususunya dibidang pelajaran PAI umumnya bagi pelajaran yang lainnya, sehingga dapat bermanfaat juga bagi sekolah-sekolah lain pada umumnya. Kata Kunci : Model Pembelajaran Talking Stick, Hasil Belajar.